Այսրկովկասի 1867 թ. վարչական բարեփոխման լուսաբանումը և գնահատումը պատմագիտության մեջ - Արամ Հակոբյան (ՀՀ ԳԱԱ հրատ.)
Проблема освещения и оценки управленческой реформы 1867 г. в Закавказье является предметом различных толкований. Несмотря на то, что во многих исследованиях недооценивается значение реформы как акта, который немного упростил систему кавказского управления, ослабил влияние наместника на гражданское управление, в большинстве взгляды исследователей в основном одинаковы. Обосновывая необходимость реформы, они в общем отрицательно оценили ее результаты. The problem of illumination and evaluation of the 1867 administrative reform has been the subject of different interpretations. Despite the fact that a good deal of opinions reflect the underestimation of the reform’s importance – as a measure which considerably simplified the system of Caucasian administration, as well as weakened the influence of the local governor, in general, most of the authors agree with each other. More particularly, trying to justify the necessity of the reform, the authors, on the whole, evaluated it as a negative phenomenon.
Keywords: History; D History